2020 42nd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2020
DOI: 10.1109/embc44109.2020.9175737
|View full text |Cite
|
Sign up to set email alerts
|

RF heating of deep brain stimulation implants during MRI in 1.2 T vertical scanners versus 1.5 T horizontal systems: A simulation study with realistic lead configurations

Abstract: Patients with deep brain stimulation (DBS) implants are often denied access to magnetic resonance imaging (MRI) due to safety concerns associated with RF heating of implants. Although MR-conditional DBS devices are available, complying with manufacturer guidelines has proved to be difficult as pulse sequences that optimally visualize DBS target structures tend to have much higher specific absorption rate (SAR) of radiofrequency energy than current guidelines allow. The MR-labeling of DBS devices, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…As a result, researchers have resorted to application of MRI beyond the currently approved labeling of the device based on RF heating assessment through phantom experiments or numerical simulations. These studies, however, have focused on 1.2T, 1.5T and 3T scanners due to their clinical prevalence [ 10 , 58 62 ]. This work presents the first study of MRI safety in patients with DBS implants at 7T, and as such, provides a frame of reference to compare risks and benefits of ultra-high field MRI in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, researchers have resorted to application of MRI beyond the currently approved labeling of the device based on RF heating assessment through phantom experiments or numerical simulations. These studies, however, have focused on 1.2T, 1.5T and 3T scanners due to their clinical prevalence [ 10 , 58 62 ]. This work presents the first study of MRI safety in patients with DBS implants at 7T, and as such, provides a frame of reference to compare risks and benefits of ultra-high field MRI in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary simulation study with three simplified DBS lead models, we showed that a vertical butterfly coil generated 4‐ to 14‐fold lower SAR at tips of implanted leads compared to a horizontal birdcage coil 11 . Later, we extended the study to include 40 lead models based on images of patients with lead‐only DBS systems which confirmed a significant reduction in RF heating 12 . Here, we report results of an expanded study on 90 patient‐derived DBS lead models including both lead‐only and fully implanted systems.…”
Section: Introductionmentioning
confidence: 76%
“…11 Later, we extended the study to include 40 lead models based on images of patients with lead-only DBS systems which confirmed a significant reduction in RF heating. 12 Here, we report results of an expanded study on 90 patient-derived DBS lead models including both lead-only and fully implanted systems. New patients were recruited from a second DBS center to account for the surgeon-dependent variability in routing of DBS leads.…”
Section: Introductionmentioning
confidence: 99%
“…cardiac pacemaker and electrode). [94][95][96][97][98][99][100] MR unsafe corresponds to materials that are dangerous in MR environments, such as surgical scissors and forceps. [101][102][103][104] Preventing eddy current-induced complications in the patient Consideration must be given to eddy currents, which are generated in nearby conductors, including the largest eddy current generated in an MR scanner, which is a shield panel placed inside the gradient coil, which is part of the MR scanner, and when there is ferrous, eddy current is not the only cause of heat generation but also there is so-called antenna effect and current inflow.…”
Section: Intraoperative Mr Imaging Past and Presentmentioning
confidence: 99%